Reflexiones sobre el TLC entre Estados Unidos y Colombia : exportaciones del sector de textiles y confecciones Colombiano (1995-2013 (2014)
This research studies the past and future behavior of exports of the main links of the Colombian textile and clothing sector, within the framework of the TLC-col-us. By using the Markov-switching models it is revealed that With the entry into force of the FTA, exports from the sector have not entered a path of growth that pushes them above their historical values, and there is also a low probability that they will enter a path of expansion.